Polymorphisms in the SP110 and TNF-α Gene and Susceptibility to Pulmonary and Spinal Tuberculosis among Southern Chinese Population - Zhou, Ying; Tan, Chun-yan; Mo, Zhi-jiang; Gao, Qi-le; He, Dan; Li, Jiong; Huang, Rong-fu; Li, Yan-bing; Guo, Chao-feng; Guo, Qiang; Wang, Long-jie; Yang, Guan-teng; et al. (Disease Markers, 2017)
Objective. To investigate the association of single-nucleotide polymorphisms (SNPs) in SP110 gene and TNF-α gene among pulmonary TB (PTB) and spinal TB (STB) patients. Methods. In a total of 190 PTB patients, 183 STB patients were enrolled as the case group and 362 healthy individuals at the same geographical region as the control group. The SP110 SNPs (rs722555 and rs1135791) and the promoter -308G>A (rs1800629) and -238G>A (rs361525) polymorphisms in TNF-α were genotyped. Results. TNF-α -238G>A polymorphism was involved in susceptibility to STB, but not to PTB. The TNF-α -238 A allele was a protective factor against STB (A versus G: OR [95% CI] = 0.331 [0.113–0.972], P=0.044). Furthermore, the presence of the -238 A allele was considered a trend to decrease the risk of STB (AG versus GG: P=0.062, OR [95% CI] = 0.352 [0.118–1.053]; AA + AG versus GG: P=0.050, OR [95CI%] = 0.335 [0.113–0.999]). However, SP110 SNPs (rs722555 and rs1135791) and TNF-α -308G>A (rs1800629) showed no association with PTB and STB in all genetic models. Conclusion. The TNF-α -238 A allele appeared a protective effect against STB, whereas the SP110 SNPs (rs722555 and rs1135791) and TNF-α -308G>A (rs1800629) showed no association with susceptibility to PTB and STB patients in southern China.